Age-Related Metabolic Pathways Changes in Dental Follicles: A Pilot Study - Bastos, Victor Coutinho; Vitório, Jéssica Gardone; Martins-Chaves, Roberta Rayra; Leite-Lima, Flávia; Lebron, Yuri Abner Rocha; Moreira, Victor Rezende; Duarte-Andrade, Filipe Fideles; Pereira, Thaís dos Santos Fontes; Santos, Lucilaine Valéria de Souza; Lange, Liséte Celina; Macedo, Adriana Nori de; Canuto, Gisele André Baptista; et al. (Frontiers in Oral Health, 2021)
Aging is not a matter of choice; it is our fate. The 'time-dependent functional decline that affects most living organisms' is coupled with several alterations in cellular processes, including cell senescence, epigenetic alterations, genomic instability, stem cell exhaustion, amongst others. Age-related morphological changes in dental follicles have been investigated for decades, mainly motivated by the fact that cysts and tumors may arise in association with a unerupted and/or impacted teeth. The more we understand dental follicles’ physiology, the more we become able to contextualize biological events that can be associated with the occurrence of odontogenic lesions which incidence increases with age. Thus, our objective was to assess age-related changes in metabolic pathways of dental follicles associated with unerupted/impacted mandibular third molars from young and adult individuals. For this purpose, a convenience sample of formalin-fixed paraffin-embedded dental follicles from young (<16 y.o., n = 13) and adult (>26 y.o., n = 7) individuals was selected. Samples were analyzed by high-performance liquid chromatography-mass spectrometry (HPLC-MS)-based untargeted metabolomics. Multivariate and univariate analyses were conducted, and the prediction of altered pathways was performed by mummichog and GSEA approaches. Dental follicles from young and older individuals showed differences in pathways related to C21-steroid hormone biosynthesis, bile acid biosynthesis, galactose metabolism, androgen and estrogen biosynthesis, starch and sucrose metabolism and lipoate metabolism. We conclude that metabolic pathways differences related to aging, were observed between dental follicles from young and adult individuals. Our findings support that similar to other human tissues, dental follicles associated with unerupted tooth show alterations at a metabolic level with aging, which can pave the way for further studies on oral pathology, oral biology and physiology.